Development and Acceptability of Dragon Fruit Wine - Bautista, Rosalyn L. (International Journal of Psychosocial Rehabilitation, 2020)
The wine making is an activity being performed by the students in Organic Chemistry class to relate the concept of Organic Reactions to real life situations. The study attempts to develop wine from red variety of dragon fruit (Hylocereus polyrhizus) and determine its acceptability through sensory evaluation. There were 29 Faculty and Staff of the Isabela State University who were purposively selected as evaluators. By Steam distillation, the volume percent of the product was 12.38% (g/100 ml). For the sensory characteristics, it has an excellent rating in terms of clarity with verbal interpretation as brilliant with outstanding characteristics color. Moreover, rated as good for its pleasant aftertaste, characteristic aroma , distinguishable bouquet and balanced. A positive correlation on their educational background and frequency of drinking alcoholic beverages with r=0.400 and negative correlation to the aroma and bouquet with r= -0.400. Finally, a positive correlation between the appearance and overall impression with r=0.400.